^3ab^2-5ab^3-3ab^2+5b^3a-8a^3b^2+8a^2b^3化简
1个回答
3ab^2-5ab^3-3ab^2+5b^3a-8a^3b^2+8a^2b^3?
=3ab^2-3ab^2-5ab^3+5ab^3
=0+0+8a^2b^3-8a^3b^2
=8a²b²(b-a)
相关问题
化简5ab-[2(2a²-ab-b²)-3(a²+b²)]-3(ab-2b&su
1.化简2ab²+3a²b-½a²b⊙2.(8a²b-5ab²
化简 3a2-ab/3a2+5ab-2b2
化简[2/b*√(ab^5)]*(-2/3*√a^3b)÷3√(b/a)
3a^2-5a∧2+ab-b^2-7ab+7b^2+3a∧2=?化简
1、化简求值:(8a^2-2b^2)/((4a^2b+4ab^2+b^3)/(2b^2-5ab-3a^2))*(b/(b
化简 2a-(5ab+b)+(3a-4b-ab)
化简ab-2{ab-[3a²b-(4ab²+2/1ab)-3a²b]}-3ab²
化简ab-[3a^2b-(2/3ab+4a^2b)]-(2ab+a^2b)
化简ab-[3a^2b-(2/3ab+4a^2b)]-(2ab+a^2b)